Staphylococcus aureus infections in newborns - Riboli, Danilo Flávio Moraes [UNESP]; Barbosa, Thaís Alves [UNESP]; de Lourdes Ribeiro de Souza da Cunha, Maria [UNESP] (My University, 2021)
The prevention and control of bacterial infections in newborns represents a challenge for health professionals. Outbreaks of infection in premature newborns (NBs), after colonization, have been widely reported to cause large numbers of deaths. It is known that in neonates, bacterial colonization begins shortly after birth, characterized by the presence of the microorganism in the host without clinical manifestations or immune responses. The primary risk factors for infection in NBs include colonization, prematurity, low birth weight, immaturity of the immune system, prolonged hospital stays, the use of antimicrobials and invasive procedures and/or surgery. Among the pathogens most commonly associated with colonization and infection in Neonatal Intensive Care Units (NICU) are the species of the Staphylococcus genus, among which Staphylococcus aureus is considered the most important pathogen of the genus, able to cause numerous infectious processes with multiple clinical symptomatologies, from localized diseases to systemic frameworks. The methicillin-resistant Staphylococcus aureus (MRSA) is included as an integral part of this group, one of the main pathogens in nosocomial infections, with prevalence of 1.5% in neonates in NICUs and 3% in children in Pediatric Intensive Care Units. In catheter related bloodstream infections, the Centers of Disease Control data report the coagulase-negative staphylococci as the most common pathogens, followed by S. aureus, Enterococcus and Candida species. Neonatal sepsis is classified according to the onset of the disease. It is called early onset when it occurs in the first week of life, and late onset when it occurs between the first week and the end of the neonatal period and can be defined clinically, diagnosed through a combination of clinical signs (such as thermal instability, bradycardia, apnea, hypoactivity/lethargy, food intolerance), and/or microbiologically confirmed through laboratory tests and detection of bacteria in the blood culture. Together with the sepsis syndrome, meningitis can occur both early and late and the clinical presentation may be indistinguishable from neonatal sepsis. Due to the clinical importance, increased morbidity and mortality, this chapter aims at discussing the epidemiological role of S. aureus in infections in NBs, through colonization, pathogenicity, diagnosis and treatment.